Overview of A Nurse In Implementing 5 Moments of Hand Washing in the Prevention of Nosocomial Infection - Aeni, Qurrotul; Anggraeni, Rina; Nurwijayanti, Andriyani Mustika (Global Health Science Group, 2024)
Behaviors to prevent the spread of disease from person to person or from equipment to person can be carried out by placing a barrier between the microorganism and the individual (patient or health worker). The barrier can be physical effort in the form of washing hands. There are